Bond behavior between ASR-damaged concrete and CFRP sheets: Empirical modeling. (May 2020) - Haddad, Rami H.; Al-Sayed, Ahmad
Abstract: Bond behavior between concrete, which has been cracked by alkali-silica reaction (ASR), and fiber-reinforced concrete polymer (CFRP) sheets is investigated with double-lap shear specimens, assembled using concrete blocks (150x200 × 150 mm 3 ) and CFRP sheets at various bond lengths and widths. The blocks were cast with reactive silica particles before being treated in a sodium hydride solution to accelerate ASR; others were prepared using non-reactive particles and kept in lime water as controls. Empirical models were developed to predict bond force based on the present data. Results show significant reductions in the ultimate bond force (reaching about 69%) as ASR progresses. Highlights: Bond characteristics between CFRP and concrete were determinately affected by ASR. Dimensions of CFRP sheets affected the percentage reduction in bond due to ASR. Bond models developed showed higher precision as compared to those in literature.